PENGUASAAN KOSAKATA BAHASA JEPANG SISWA SMAN 9 PEKANBARU - Nova Mahelna Br Sirait; Nana Rahayu; Sri Wahyu Widiati (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2022)
Abstract: This study aims to determine the level of Japanese vocabulary mastery of class XI students of SMAN 9 Pekanbaru. This study uses a quantitative descriptive research method. The population is class XI SMAN 9 Pekanbaru with a sample of 30 students. The instrument of this research is a test. The data analysis technique used SPSS Version 25. The results showed that the level of mastery of Japanese vocabulary at SMAN 9 Pekanbaru students got an average score of 66.00 with less category.Key Words: Mastery, Vocabulary, Japanese